IMPACT OF FISHING AND HABITAT DEGRADATION ON THE DENSITY OF BANGGAI CARDINAL FISH (Pterapogon kauderni, Koumans 1933) IN BANGGAI ARCHIPELAGO, INDONESIA - Kamaluddin Kasim; Sri Turni Hartati; Prihatiningsih Prihatiningsih; Gudmundur Thordarson (Research Center for Fisheries, 2014)
Banggai cardinal fish (Pterapogonkauderni, Koumans 1933) is uncommon example of a marine fish with distributed in small range area while being in highly exploited. This fish is in high demand as an ornamental fish. However, the information on the number of density is limited. An underwater visual fish census survey was conducted in June to July 2010 at 18 fishing sites around Banggai archipelago to estimate the density of the stock and assess the impact of fishing and habitat on density. The areas are divided into three main islands, namely Banggai Island, Peleng Island, Toropot-Tumbak-Labobo Island. The lowest density index of the P. kauderni recorded at Kindandal village on Peleng Island, 0.014 fish/m2while the highest abundance index of 3.0 fish/m2 found at Toropot village at Toropot Island. In three survey sites (Bonebaru and Toropot villages) where the fishing activities are still ongoing, the density has declined compared to the survey conducted in 2004. Majority of the villages in Peleng Island have lower density compared with the other islands probably due to the degradation of microhabitat of P. kauderni. In many cases, microhabitat degradation might be as a result of collection of sea urchins and sea anemone for consumption by local community.